Penggunaan Metode Eksperimen dapat Meningkatkan Pemahaman Siswa Tentang Konsep Pesawat Sederhana pada Mata Pelajaran IPA SDN. No. 033/XI Tanjung Muda Tahun 2016/2017 - Emi Nofrida (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Science learning in elementary schools is the important foundation in instilling scientific knowledge, skills, and attitudes. However, one of the problems faced by teachers in elementary schools is that students have difficulty understanding concepts in science subjects which result in low learning outcomes. This study aims to improve students' understanding of the concept of simple aircraft in science subjects by using experimental methods. The research is a classroom action research involving 20 students of fifth grade year 2016/2017 in SDN. No. 033/XI Tanjung Muda, Hamparan Rawang Subdistrict, Sungai Penuh City, Jambi Province. This research was conducted from January to May 2017. This research was conducted in two cycles and each cycle consisted of two meetings with four activities namely planning, implementation, observation, and reflection. Understanding of concepts is measured by student activity in class and learning outcomes. Data was collected by tests and observations. Data was processed and analyzed by descriptive analysis and simple statistical test. The results showed that the use of experimental methods can improve the understanding of students about the concept of simple aircraft. The use of experimental methods increases students’ activity and learning outcomes. Increased student learning activity seen from the increasing percentage of students who ask questions, working together in groups, able to conduct experiments independently, cleaning and storing tools and materials that have been used in the experiment, and deliver the results of experiments. The results showed that the mean grade increased from 47,5 (before action) to 60,5 (cycle I) and 75,0 (cycle II). The percentage of completed students in learning also increased from 45,0% (before action) to 60,0% (cycle I) and 85,0% (cycle II). Thus, the experimental method can be an alternative in improving students' understanding of the concept in science subjects.